Implementasi Peran Asosiasi Cerdas dan Berbakat Istimewa (CI+BI) Nasional Dalam Peningkatan Mutu Layanan Pendidikan Untuk Siswa Cerdas dan Berbakat Istimewa (CI+BI) Indonesia - Intan Larange Arifin; Amril Muhammad; Siti Rochanah (Program Studi Manajemen Pendidikan, 2016)
This research was conducted at Asosiasi CI+BI Nasional, which aims to determine the process of teamwork and communication is done Asosiasi CI+BI Nasional in improving the quality of educational services for gifted students and special intelligent Indonesia. This study was conducted in November 2015 and January 2016. The researchers used a qualitative approach and descriptive method. Data collected through interviews, observation, and documentation study. Source data from this study are: the general secretary of the Asosiasi CI+BI Nasional, chairman of the Asosiasi CI+BI Wilayah, and some informants supporting, among others, the management areas of the Asosiasi CI+BI Nasional and school/madrasah service provider subsidiary CI+BI under the auspices of the Asosiasi CI+BI Nasional. Teamwork in Asosiasi CI+BI Nasional is done by those who want to work together to analyze needs and the resources available for cooperation with Asosiasi CI+BI Nasional. Then those who want to work together to contact Asosiasi CI+BI Nasional and did a deal related to the program to be implemented. Asosiasi CI+BI Nasional provides guidance to those who want to work together to reach areas of Asosiasi CI+BI Nasional in accordance with the needs and demands. Asosiasi CI+BI Nasional should help schools/madrasah service provider subsidiary CI+BI to look for students who have the potential of gifted special use technology optimally to notify information about the achievements of students CI+BI by making connections between blogs Asosiasi CI+BI Nasional website owned by the school/madrasah service provider CI + BI children under the auspices of Asosiasi CI+BI Nasional.